An Evaluation of Frozen Section and Lymph Node Dissection Results for Mucinous Ovarian Tumors. Issue 1 (1st January 2018) - Moroney, Marisa R.; Post, Miriam D.; Berning, Amber A.; Sheeder, Jeanelle; Corr, Bradley R.
Abstract : Objectives: Intraoperative frozen section has greater than 90% accuracy for ovarian tumors; however, mucinous histology has been shown to be associated with increased frozen section inaccuracy. Recent data demonstrate that primary ovarian mucinous carcinomas have no lymph node involvement, even when extraovarian disease is present, and therefore may not require lymph node dissection. Our primary objective is to evaluate the accuracy of identifying mucinous histology on frozen section. Methods/Materials: A cross-sectional review of mucinous ovarian tumors in surgical patients at one institution from 2006 to 2016 was performed. Cases reporting a mucinous ovarian tumor on frozen section or final pathology were identified. Frozen section results were compared with final diagnosis to calculate concordance rates. Analyses with χ 2 and t tests were performed to identify variables associated with pathology discordance. Results: A total of 126 mucinous ovarian tumors were identified. Of these, 106 were reported as mucinous on frozen section and 103 (97.2%) were concordant on final pathology. Discordant cases included 2 serous and 1 clear cell tumor. Among the 103 mucinous tumors, classification as malignant, borderline, or benign was concordant in 74 (71.8%) of 103 cases, whereas 22 (21.4%) of 103 were discordant and 7 (6.8%) were deferred to final pathology. Lymph node dissection was performed in 33 cases; the only case with lymph node metastasis was a gastrointestinal mucinous adenocarcinoma. Discordance between frozen section and final pathology was associated with larger tumor size and diagnosis other than benign: discordant cases had a mean tumor size of 21.7 cm compared with 14.4 cm for concordant cases ( P < 0.001), and 93.5% of discordant cases were borderline or malignant, compared with 30.5% of concordant cases ( P < 0.001). Conclusions: Intraoperative identification of mucinous histology by frozen section is reliable with a concordance rate to final pathology of 97.2%. No lymph node metastases were present in any malignant or borderline primary ovarian cases.